Role of Forming Aggregates in Post-Thaw Survival of Isolated Neural Cells from Newborn Rats - Sukach, A. N.; Lyashenko, T. D. (Problems of Cryobiology and Cryomedicine, 2011)
The role of formation of newborn rat neural cell aggregates on cell recovery after isolation and cryopreservation was studied. Short-term cultivation of neural cells within aggregates eliminate the damages that appear during cell isolation and possibly protects from apoptosis. It was shown that freezing of neural cells within aggregates under protection of 10% DMSO is effective for storage of stem/progenitor and differentiated neural cells. Maintenance of integrity of neural cell aggregates after cryopreservation is a necessary condition for survival in culture.